Soybean continuous cropping affects yield by changing soil chemical properties and microbial community richness - Li, Yan; Shi, Chuanqi; Wei, Dan; Gu, Xuejia; Wang, Yufeng; Sun, Lei; Cai, Shanshan; Hu, Yu; Jin, Liang; Wang, Wei (Frontiers in Microbiology, 2022)
Abstract: In agroecosystems, different cropping patterns cause changes in soil physicochemical properties and thus in microbial communities, which in turn affect crop yields. In this study, the yields of soybean continuous cropping for 5 years (C5), 10 years (C10), and 20 years (C20) and of soybean-corn rotational cropping (R) treatments were determined, and samples of the tillage layer soil were collected. High-throughput sequencing technology was used to analyze the diversity and composition of the soil bacterial and fungal communities. The factors influencing microbial communities, along with the effects of these communities and those of soil chemical indexes on yield, were further evaluated. The results showed that the community richness index of bacteria was higher in C20 than in R and that of fungi was highest in C5. The differences in the bacterial and fungal communities diversity indexes were not significant among the different continuous cropping treatments, respectively. The soil microbial community composition of all continuous cropping treatments differed significantly from R. The dominant bacterial phylum was Actinobacteriota and the dominant fungal phylum was Ascomycota. The relative abundance of Fusarium did not differ significantly among the continuous cropping treatments, while that of the plant pathogen fungi Lectera sp., Plectosphaerella sp., and Volutella sp. increased with continuous cropping years. Soil pH, SOM, N, and TP had significant effects on both bacterial and fungal communities, and TK and C/N had highly significant effects on fungal communities. The yield of C5 was significantly lower than that of R, and the differences in yield between C10, C20, and R were not significant. TN, TP, and pH had significant effects on yield, and fungal community abundance had a greater negative effect on yield than bacterial community abundance.